Use of clinical vignette questionnaires to investigate the variation in management of keratoconjunctivitis sicca and acute glaucoma in dogs - White, C.N.; Downes, Martin J.; Jones, G.; Wigfall, C.; Dean, Rachel S.; Brennan, Marnie L. (BMJ Publishing Group, 2018)
There is little peer-reviewed research assessing therapeutic effectiveness in canine eye disease. Current treatments used in first opinion and ophthalmology referral practices are also somewhat poorly documented. The aim of this study was to investigate the current management of canine keratoconjunctivitis sicca (KCS) and acute primary angle-closure glaucoma (PACG) by veterinary surgeons. Questionnaires using clinical vignettes were administered to a cross section of general practitioners (‘GPs’) and veterinarians engaged in or training for postgraduate ophthalmology practice (’PGs’). Similar treatment recommendations for KCS (topical cyclosporine, lubricant, antibiotic) were given by both groups of veterinarians with the single exception of increased topical antibiotic use by GPs. Treatment of acute glaucoma diverged between groups: PGs were much more likely to recommend topical prostaglandin analogues (PGAs) and a wider array of both topical and systemic treatments were recommended by both groups. Systemic ocular hypotensive agents were suggested infrequently. Our results suggest that treatments may vary substantially in ocular conditions, particularly in conditions for which neither guidelines nor high quality evidence exists. This study highlights the need for novel strategies to address evidence gaps in veterinary medicine, as well as for better evaluation and dissemination of current treatment experience.